(untitled) (Journal of Pathology of Nepal, 2020)
Background: Plasma fibrinogen is an indicator of inflammation and endothelial dysfunction has been described as an independent risk factor for cardiovascular morbidity in type 2 Diabetes mellitus patients. Poor glycemic control has been reported to be associated with hyperfibrinogenemia and its complications. This study was aimed to find a correlation of mean fibrinogen level with glycemic control in complicated and uncomplicated cases of Type 2 Diabetes mellitus. Materials and methods: One hundred eight known cases of Type 2 Diabetes mellitus aged ≥ 30 were included in our study of which 39 cases were uncomplicated and 69 cases were complicated Diabetes mellitus. Hundred of non-diabetic age and sex-matched controls were analyzed. Blood samples were collected in Ethylenediaminetetraacetic acid and citrate bulb for estimation of HbA1c and plasma fibrinogen level respectively. Results: Mean fibrinogen level in complicated Type 2 Diabetes mellitus was high 450.43 ±108.51 mg/dl as compared to uncomplicated cases 372.30±123.78 mg/dl (p=0.0001). Mean HbA1c in total Diabetes mellitus cases was 8.02±1.88 mg/dl with a range of 5.50-14.50 mg/dl. A positive correlation was found between HbA1c and mean fibrinogen level (r=0.782, p= 0.001) in type 2 Diabetes mellitus. Duration of diabetes in years showed a significant correlation with mean fibrinogen levels (r=0.295, p=0.002). Conclusions: Plasma fibrinogen level was significantly associated with glycemic control (HbA1c) and duration of Diabetes mellitus in years. Thus, lowering plasma fibrinogen levels could be an important approach to the prevention of cardiovascular complications in diabetics.